Professional Islamic Education Teacher in Pesantren on Imam Al-Murtadla Az-Zabidi's Perspective (An Analysis of Ithafu As-Sa'adah Al-Muttaqin) - Mu'ammar, Muhammad Arfan; Muchtar, Nicky Estu Putu (At-Ta'dib, 2025)
Purpose -Teachers in Islamic boarding schools (pesantren) play a central role not only in transferring knowledge but also in shaping students’ character and spiritual growth. This study explores the concept of a professional Islamic education teacher from the perspective of Imam al-Murtadla az-Zabidi in his seminal work Ithaf al-Sadah al-Muttaqin, with the aim of assessing its relevance to the professional standards of modern educators. Methods - Utilizing a qualitative library research method, the study conducts a critical textual analysis of Imam al-Zabidi's views and compares them with both classical and contemporary perspectives on teacher professionalism. Findings - indicate that a professional Islamic education teacher, according to Imam al-Zabidi, must embody four key competencies professional, pedagogical, personal, and social while internalizing their dual role: serving as both a devotional servant of Allah and a khalifah on Earth. Imam al-Zabidi emphasizes the teacher's responsibilities to act as a parental figure, a prophetic successor, a moral guide, and a consistent role model who practices what they teach. The teacher must tailor instruction to students’ capacities, guide against moral decay with wisdom, and maintain ethical humility rooted in the pursuit of divine truth. Implications - of this study suggest that classical Islamic educational thought especially as framed by Imam al-Zabidi offers a rich normative framework for addressing today’s educational challenges, particularly in the moral and spiritual domains. However, the research is limited in scope to the pesantren context and classical text interpretation, warranting further empirical validation in diverse educational environments. Originality/value lies in the study’s contribution to bridging classical Islamic scholarship and contemporary educational theory, offering an integrative model of professional teacher identity grounded in Islamic ethics and character-based pedagogy.